MUHAMMAD SA’ID AL-‘ASHMAWI (Mencabar Pemikirannya tentang Penerapan Syarî’ah di Mesir) - Moh. Hefni (Al-Ihkam: Jurnal Hukum dan Pranata Sosial)
The rise of a vigorous and sometimes violent Islamist movement in Egypt has attracted considerable attention from scholars. Less attention has been given to those who have responded to this challenge at the level of ideological debate. One of these is a prominent judge, Muhammad Sa’id al-‘Ashmawi. He argues that the call for the "application of the syarî’ah" (tathbîq al-sharî’ah), watchwords of the Islamist movement, are in reality little more than empty slogans, designed to get popular support for a political venture but extremely vague and probably insignificant in substance. In time, however, its meaning expanded, first to include all of the rules for worship and society found in the Qur’ân, then those in the sunna of the Prophet, and finally all the opinions and judgments of the scholars (ijtihâd). But these opinions and judgments are properly called fiqh, and the final result of the development is that in common usage the term syarî’ah has come to mean fiqh.Those who use the slogan, however, are in fact calling for the application oí fiqh, that is, a set of rules and laws devised by humans, not God, to meet historical conditions of the past which no longer obtain. In discussing ribä, al-cAshmawi holds that current Egyptian law essentially conforms to the syarî’ah. The same is true of the rest of Egyptian law.